(untitled) (Journal of Oriental Studies, 2018)
This paper provides geopolitical views on the Caspian Sea. There is also analysis of western classical geopolitical works. The works of scientists who have not eliminated their relevance and have played a role in geopolitics are now the most prominent works leading western foreign policy. The geographical scope of the Caspian Sea and its region is important in the international arena. The energy strategies of countries that have access to the energy-rich sea and its region have also been analyzed. The geopolitical landscape of the Cold War, especially geopolitical scholars, has continued with ideological theories.